PEREMPUAN DALAM PERKEMBANGAN ILMU PENGETAHUAN DAN TEKNOLOGI - Wakhidah, Nur (Pusat Studi Gender UIN Maulana Malik Ibrahim Malang, 2009)
The development of science and technology influence all aspects of life. The development is not only dominated by men but also by women. Women are considered as the user of the invention of science and technology while men are the inventor. Men, explicitly, pose role in the process of science and tech- nology. However, scientists propose findings that show womenâ€™s identity of technology. It is predicted by those who are concerned with women issues that there will be more women involving in the process of inventions in sci- ence and technology. This achievement of women is inevitable as they have contributed much on theÂ development of that area whether it is publicly accepted or not.Keywords: Perempuan, Perkembangan, Ilmu Pengetahuan dan Teknologi